Diagnostic potential of plasma microRNA signatures in patients with deep-vein thrombosis - Wang, Xiao; Sundquist, Kristina; Elf, Johan L.; Strandberg, Karin; Svensson, Peter J.; Hedelius, Anna; Palmér, Karolina; Memon, Ashfaque A.; Sundquist, Jan; Zöller, Bengt (Thrombosis and Haemostasis, 2016)
For excluding deep-vein thrombosis (DVT), a negative D-dimer and low clinical probability are used to rule out DVT. Circulating microRNAs (miRNAs) are stably present in the plasma, serum and other body fluids. Their diagnostic function has been investigated in many diseases but not in DVT. The aims of present study were to assess the diagnostic ability of plasma miRNAs in DVT and to examine their correlation with known markers of hypercoagulability, such as D-dimer and APC-PCI complex. Plasma samples were obtained from 238 patients (aged 16–95 years) with suspected DVT included in a prospective multicentre management study (SCORE). We first performed miRNA screening of plasma samples from three plasma pools containing plasma from 12 patients with DVT and three plasma pools containing plasma from 12 patients without DVT using a microRNA Ready-to-use PCR Panel comprising 742 miRNA primer sets. Thirteen miRNAs that differentially expressed were further investigated by quantitative real-time (qRT)-PCR in the entire cohort. The plasma level of miR-424–5p (p=0.01) were significantly higher, whereas the levels of miR-136–5p (p=0.03) were significantly lower in DVT patients compared to patients without DVT. Receiver-operating characteristic curve analysis showed the area under the curve (AUC) values of 0.63 for miR-424–5p and 0.60 for miR-136–5p. The plasma level of miR-424–5p was associated with both D-dimer and APC-PCI complex levels (p<0.0001 and p=0.001, respectively). In conclusions, these findings indicate that certain miRNAs are associated with DVT and markers of hypercoagulability, though their diagnostic abilities are probably too low.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Deep venous thrombosis; microRNA; diagnosis; D-dimer; APC-PCI complex